Exploring Challenges Faced by EFL Learners in Pakistani Traditional Classrooms: Insights from Teachers’ Perspectives - Malik, Maryam; Nayab, Durr-e- (Pakistan Journal of Humanities and Social Sciences, 2024)
This research aims to ascertain the difficulties experienced by EFL learners in traditional classroom environments from the EFL teachers’ viewpoint. In the present study, quantitative research method has been adopted, and participants were comprised of 150 EFL teachers taken from Multan District using structured questionnaire. The study points out barriers to learning: language barriers, cultural barriers, and instructional barriers. Furthermore, the work explores how teachers manage to overcome the stated difficulties with a focus on the motivation and engagement processes. The study shows a difference in the classroom environment involving EFL learners and their teaching methodology, and the results signify a need for variation in teaching strategies to suit the EFL learners. In keeping with the practical nature of this study, the researcher is determined to improve the teaching contexts for EFL by refining best practices for constructionist teaching, strengthening the learners’ content knowledge, and expanding the research and practices in the field of EFL. The findings of this study provide useful recommendations for any educator who could attempt to navigate the difficulties that come with EFL education.